CURRENT NEEDS FOR FURTHER DEVELOPMENT OF SERBIAN LABOUR LEGISLATION - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Current needs for further development of Serbian legislation relate to the field of collective employee-employer relations and their collective rights and obligations. These are the relations established by the workers’ and employers’ mutually, but also the relationship between them, on the one hand and the state on the other. In other words, this is the need to strengthen the industrial democracies (including the improvement of labour legislation in the field of collective rights of employees and employers, which is actually still in stagnation. The fact is that trade union movement in Serbia, social dialogue, collective bargaining on working conditions, employees participation in management are weakening, which is where one should seek current needs for further development of labour law in order to strengthen and provide normatively the legal platform to stop these negative tendencies. Key words: trade union freedoms and rights, social dialogue, collective bargaining, employee participation in management, industrial democracy, ownership transition, transition, labour legislation.